The geriatric 5Ms, artificial intelligence, and Hannah Arendt’s critique: ethical reflections within contemporary gerontology - Virgílio Garcia Moreira; Andréia Pain; Ivan Aprahamian (Geriatrics, Gerontology and Aging)
The intersection of geriatrics, artificial intelligence (AI), and ethics presents a growing challenge in the field of aging medicine. The Geriatric 5Ms framework — Mind, Mobility, Medications, Multicomplexity, and Matters Most — guides current clinical practice in the approach to older patients. The integration of AI into geriatrics has the potential to improve diagnostic accuracy, optimize therapies, and individualize interventions. However, the automation of clinical decision-making carries inherent ethical risks, potentially reducing the patient to a set of data and weakening the physician-patient relationship. Hannah Arendt’s critique of the bureaucratization of thought and the banality of evil warns of the dangerous alienation of healthcare professionals in the face of uncritical reliance on algorithms. This article proposes a critical approach to the use of AI in geriatrics, emphasizing the need for a balance between technology and clinical judgment. The regulation of these technologies should prioritize equity, personalized care, and professional autonomy, ensuring that technological innovation reinforces — rather than replaces — patient-centered medical practice.